Wearable, battery-free, wireless multiplexed printed sensors for heat stroke prevention with mussel-inspired bio-adhesive membranes - Maroli, Gabriel (2024)
Wearable technologies are becoming pervasive in our society, and their development continues to accelerate the untapped potential of continuous and ubiquitous sensing, coupled with big data analysis and interpretation, has only just begun to unfold. However, existing wearable devices are still bulky (mainly due to batteries and electronics) and have suboptimal skin contact. In this work, we propose a novel approach based on a sensor network produced through inkjet printing of nanofunctional inks onto a semipermeable substrate. This network enables real-time monitoring of critical physiological parameters, including temperature, humidity, and muscle contraction. Remarkably, our system operates under battery-free and wireless near-field communication (NFC) technology for data readout via smartphones. Moreover, two of the three sensors were integrated onto a naturally adhesive bioinspired membrane. This membrane, developed using an eco-friendly, high-throughput process, draws inspiration from the remarkable adhesive properties of mussel-inspired molecules. The resulting ultra-conformable membrane adheres effortlessly to the skin, ensuring reliable and continuous data collection. The urgency of effective monitoring systems cannot be overstated, especially in the context of rising heat stroke incidents attributed to climate change and high-risk occupations. Heat stroke manifests as elevated skin temperature, lack of sweating, and seizures. Swift intervention is crucial to prevent progression to coma or fatality. Therefore, our proposed system holds immense promise for the monitoring of these parameters on the field, benefiting both the general population and high-risk workers, such as firefighters.